Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Let $M$ be a module with $M_1$ and $M_2$ submodules such that their sum (not necessarily a direct sum) is $M$. Is it true in full generality that $\text{Ass}(M) = \text{Ass}(M_1) \cup \text{Ass}(M_2)$? If so prove, if not, provide a counterexample.

I believe the statement is false. The fact that $\text{Ass}(M_i) \subset M$ is obvious, and I know it holds for a direct sum, however I was hoping someone could clarify with a counter example. Thanks is advance.

share|improve this question

2 Answers 2

Mariano's answer proves that if $A$ is a commutative ring and if $M_1,M_2$ are $A$-modules, then $\text{Ass}_{A}(M_1\oplus M_2)=\text{Ass}_{A}(M_1)\cup\text{Ass}_{A}(M_2)$. However, when $M$ is an $A$-module and when there exist $A$-submodules $M_1,M_2$ of $M$ such that $M=M_1+M_2$, then we cannot conclude in general that $\text{Ass}_{A}(M)=\text{Ass}_{A}(M_1)\cup\text{Ass}_{A}(M_2)$. (However, we can conclude in general that $\text{Ass}_{A}(M_1)\cup\text{Ass}_{A}(M_2)\subseteq\text{Ass}_{A}(M)$.)

Let me give a counterexample:

Exercise: Let $M=\mathbb{Z}\oplus \mathbb{Z}/2\mathbb{Z}$ be a $\mathbb{Z}$-module and let $M_1=\{(n,0):n\in\mathbb{Z}\}$, $M_2=\{(n,\overline{n}):n\in\mathbb{Z}\}$ (where $\overline{n}$ is the residue of $n$ modulo $2$).

(a) Prove that $M_1$ and $M_2$ are $\mathbb{Z}$-submodules of $M$.

(b) Prove that $M=M_1+M_2$.

(c) Prove that $M_1\cong \mathbb{Z}\cong M_2$ as $\mathbb{Z}$-modules. In particular, deduce that $\text{Ass}_{\mathbb{Z}}(M_1)=\{0\}=\text{Ass}_{\mathbb{Z}}(M_2)$.

(d) Prove that $\text{Ass}_{\mathbb{Z}}(M)=\{0,2\}$. (Hint: Mariano's answer is relevant.)

(e) Note that we have a counterexample to your claim.

I hope this helps!

share|improve this answer

$\newcommand\ass{\operatorname{Ass}}$Show that whenever you have a short exact sequence $$0\to M\to N\to P\to0$$ then $$\ass M\subseteq\ass N\subseteq\ass M\cup\ass P.$$ Then what you want follows from the existence of the two obvious exact sequences $$0\to M_1\to M_1\oplus M_2\to M_2\to0$$ and $$0\to M_2\to M_1\oplus M_2\to M_1\to0$$

share|improve this answer
    
im not talking strictly about direct sums here... –  A Sample Oct 17 '11 at 3:20

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.